COLON CAPSULE ENDOSCOPY: POSSIBILITIES OF NON-INVASIVE DIAGNOSTICS OF COLON DISEASES - E. V. Ivanova; E. D. Fedorov; E. V. Tikhomirova; A. V. Avakimyan; N. S. Marenich (Исследования и практика в медицине)
Purpose. Evaluation of feasibility of colon capsule endoscopy (CCE), as non-invasive method of diagnostics of colon abnormalities.Patients and methods. From 31.01.2014 to 10.01.2017 we successfully performed 100 CCE in 101 (99,0%) patients (m-50, f-48, mean age 44,7 ± 14,8 years, range 22–81), including 2 twins aged 8 years (CCE was performed with pediatrician). The main indication for colonoscopy was colorectal cancer screening (73 (73,0%) pts). The indication for colonoscopy to 2 twins was complicated Peutz Jeghers syndrome in one of them. CCE was performed using the system PillCam (Given Imaging) and capsule PillCam Colon 2. For the bowel preparation we used two-stage regimen; for the evaluation of preparation — J.A. Leighton scale.Results. Preparation was adequate in 88 (88,0%) pts, non-adequate — in 12 (12,0%) pts. Total CCE was performed in 82 (82,0%) patients. The mean colon transit time was 4 hours 43 min ± 3 hours15 min. Total evaluation of the colon was performed in 82 (82,0%) pts. Mucosal lesions were revealed in 75 (75,0%) pts, including epithelial polyps in 52 (69,3%) pts. We also revealed comorbid lesions in 41 (54,6%) pts. Colonoscopy after CCE was recommended to 28 (37,3%) pts because of polyp detection, sized ≥6 mm, and because of inflammatory changes of colon mucosa, but only 11 (39,3%) pts were performed colonoscopy.Conclusion. In this article the experience of colon capsule endoscopy demonstrates the principal possibility of noninvasive evaluation of the colon and detection of colon abnormalities.